2016
DOI: 10.1002/hbm.23319
|View full text |Cite
|
Sign up to set email alerts
|

Altered anterior‐posterior connectivity through the arcuate fasciculus in temporal lobe epilepsy

Abstract: How the interactions between cortices through a specific white matter pathway change during cognitive processing in patients with epilepsy remains unclear. Here, we used surface-based structural connectivity analysis to examine the change in structural connectivity with Broca’s area/the right Broca’s homologue in the lateral temporal and inferior parietal cortices through the arcuate fasciculus (AF) in 17 patients with left temporal lobe epilepsy (TLE) compared with 17 healthy controls. Then, we investigated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 98 publications
0
6
0
1
Order By: Relevance
“…First, although the statistical threshold levels used in the current study (both vertex-wise and cluster-wise thresholds less than 0.05) have also been used in other studies (e.g. (Ahveninen et al, 2013; King et al, 2015; Robinson et al, 2015; Schneider et al, 2014; Sneve et al, 2015; Takaya et al, 2016; Tchistiakova et al, 2014; Zorlu et al, 2017), we recognize those thresholds are relatively optimistic. Therefore, findings from the current study should be interpreted with caution until future studies use larger samples and more conservative thresholds (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…First, although the statistical threshold levels used in the current study (both vertex-wise and cluster-wise thresholds less than 0.05) have also been used in other studies (e.g. (Ahveninen et al, 2013; King et al, 2015; Robinson et al, 2015; Schneider et al, 2014; Sneve et al, 2015; Takaya et al, 2016; Tchistiakova et al, 2014; Zorlu et al, 2017), we recognize those thresholds are relatively optimistic. Therefore, findings from the current study should be interpreted with caution until future studies use larger samples and more conservative thresholds (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These spheres were combined with individual gray matter masks to ensure analyses did not include signals from non‐brain or white matter voxels. Variance associated with the six motion regressors was removed from the extracted time series, which was carried out to control the possible effect of head motion on the PPI results [Ries et al, ; Takaya et al, ]. For each seed mask, the time courses were then de‐convolved based on the model for the canonical hemodynamic response to construct a time series of neural activity, which was the physiological factor.…”
Section: Methodsmentioning
confidence: 99%
“…Significant gray matter atrophy (GMA) has been shown in ipsilateral extratemporal structures including ipsilateral thalamus, parietal lobe, cingulate gyrus, and regions contralateral to the epileptogenic focus, 3,7,8 which was also found to be progressive with the course of epilepsy, 9,10 even in patients with a prolonged period of seizure freedom 11 . Furthermore, studies also demonstrated disturbed functional brain networks including networks connected to the mesial temporal structures, the thalamo‐cortical circuit, default mode network (DMN) at resting state, and cognitive task‐related brain networks 12–20 …”
Section: Introductionmentioning
confidence: 99%
“…11 Furthermore, studies also demonstrated disturbed functional brain networks including networks connected to the mesial temporal structures, the thalamo-cortical circuit, default mode network (DMN) at resting state, and cognitive task-related brain networks. [12][13][14][15][16][17][18][19][20] Surgical procedures, as ATL the most adopted, are assumed to resect the most important component or the core hub of the epileptic network, rendering post-surgical seizure freedom. The brain would be reorganized structurally and functionally after surgery which may be related to postoperative seizure outcome and neuropsychological changes.…”
Section: Introductionmentioning
confidence: 99%